Distribution of tuberculosis cases in the state of Paraná: an ecological study, Brazil, 2018-2021 - Lucas Vinícius de Lima; Gabriel Pavinati; Andressa Aya Ohta; Nelly Lopes de Moraes Gil; Débora Regina de Oliveira Moura; Gabriela Tavares Magnabosco (Ministério da Saúde do Brasil, 2023)
ABSTRACT Objective: to analyze the distribution of tuberculosis cases in the state of Paraná, Brazil, between 2018 and 2021. Methods: this was an ecological study using secondary data obtained from compulsory notifications; detection rates per 100,000 inhabitants were described according to health regions in the state; percentage changes between 2018-2019 and 2020-2021 were calculated. Results: a total of 7,099 cases were registered. The highest rates were observed in the health regions of Paranaguá (52.4/100,000 in 2018-2019; 38.2/100,000 in 2020-2021) and Foz do Iguaçu (34.4/100,000 in 2018-2019; 20.5/100,000 in 2020-2021), and the lowest rates in Irati (6.3/100,000 in 2018-2019; 8.8/100,000 in 2020-2021) and Francisco Beltrão (8.5/100,000 in 2018-2019; 7.6/100,000 in 2020-2021); in 2020-2021, it could be seen a decrease in percentage changes in 18 health regions, while there was an increase in four of them, especially Foz do Iguaçu (-40.5%) and Cianorte (+53.6%). Conclusion: high rates were found in the coastal and triple border regions; and there was a decline in detection rates in the pandemic period.